2018
DOI: 10.1002/aur.2010
|View full text |Cite
|
Sign up to set email alerts
|

A matter of time: The necessity of temporal language in research on health conditions that present with autism spectrum disorder

Abstract: Research finds autistic people have more health problems than the general population but we do not understand why. In this commentary, we argue researchers need to use language describing the timing of health problems in autistic people, specifying whether problems truly co-occur (share a cause), result from autism-related disparities, or are more common in autistic people for an unknown reason. Clarifying language can provide more specificity in research and improve efforts to prevent and treat health problem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…These challenges point to the urgent need for new development and novel use of available mental health assessment schedules for people with autism and/or other neurodevelopmental disabilities. Such assessments should also incorporate a temporally focused terminology to disentangle the temporal development of CMHCs in autism, 51 to better inform causal pathways and, most importantly, clinical formulation for personalised treatment.…”
Section: Discussionmentioning
confidence: 99%
“…These challenges point to the urgent need for new development and novel use of available mental health assessment schedules for people with autism and/or other neurodevelopmental disabilities. Such assessments should also incorporate a temporally focused terminology to disentangle the temporal development of CMHCs in autism, 51 to better inform causal pathways and, most importantly, clinical formulation for personalised treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Why is autism so often accompanied by mental health, difficulties? A number of possibilities exist, which are by no means mutually exclusive (and which might be marked with more nuanced terminology; see, Rubenstein & Bishop‐Fitzpatrick, ). First, apparent ‘comorbidity’ can be due to selection bias, and additional problems may raise the likelihood of an individual requiring clinical services.…”
Section: The Changing Concept Of Autism: 6 From Pure To Complexmentioning
confidence: 99%
“…In terms of mental health conditions, findings are mixed: Nylander and colleagues (2018) identified high prevalence of affective disorders, anxiety, and psychotic disorders in older adults on the autism spectrum without co-occurring ID while Lever and Geurts (2016) found that older adults on the autism spectrum had fewer psychiatric diagnoses than young or middle aged adults on the autism spectrum. However, research in this area is still nascent and we have argued for the necessity and importance of continuing to evaluate these health conditions, incorporating a temporal and life-course perspective (Rubenstein & Bishop-Fitzpatrick, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, we see increased occurrence of epilepsy among children with autism and ID compared to children with autism alone (van Eeghen et al, 2013), which may suggest different neurological mechanisms in this subset. However, we do not know if there are health conditions intrinsically tied to autism with ID that develop later in adulthood (Rubenstein & Bishop-Fitzpatrick, 2018). Thus, assessing whether health conditions in the cohort of middle aged and older adults with autism differ between those with and without ID may help us anticipate whether future cohorts will experience similar outcomes despite different prevalence of co-occurring ID .…”
Section: Introductionmentioning
confidence: 99%